2005
DOI: 10.4049/jimmunol.175.12.8200
|View full text |Cite
|
Sign up to set email alerts
|

CD11b+/Gr-1+ Immature Myeloid Cells Mediate Suppression of T Cells in Mice Bearing Tumors of IL-1β-Secreting Cells

Abstract: Tumor cells secreting IL-1β are invasive and metastatic, more than the parental line or control mock-transfected cells, and concomitantly induce in mice general immune suppression of T cell responses. Suppression strongly correlates with accumulation in the peripheral blood and spleen of CD11b+/Gr-1+ immature myeloid cells and hematological alterations, such as splenomegaly, leukocytosis, and anemia. Resection of large tumors of IL-1β-secreting cells restored immune reactivity and hematological alterations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
248
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 276 publications
(258 citation statements)
references
References 48 publications
7
248
0
3
Order By: Relevance
“…But in contrast to IL-1α, where only increased hepatic mRNA levels were found in SDR mice, IL-1β was elevated in all three compartments analyzed including plasma protein levels. Moreover, recent studies with mice bearing tumors that overexpress and secrete IL-1β exhibited similar increases of CD11b + cells in the blood and spleen, suggesting that the mobilization of CD11b + cells in SDR mice is indeed caused by IL-1β (Song et al, 2005). However, final conclusions can only be drawn from additional experiments with IL-1α and IL-1β-deficient mice.…”
Section: Discussionmentioning
confidence: 96%
“…But in contrast to IL-1α, where only increased hepatic mRNA levels were found in SDR mice, IL-1β was elevated in all three compartments analyzed including plasma protein levels. Moreover, recent studies with mice bearing tumors that overexpress and secrete IL-1β exhibited similar increases of CD11b + cells in the blood and spleen, suggesting that the mobilization of CD11b + cells in SDR mice is indeed caused by IL-1β (Song et al, 2005). However, final conclusions can only be drawn from additional experiments with IL-1α and IL-1β-deficient mice.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, we showed that neutrophils expand in mammary tumorbearing K14-Cre;Cdh1 F/F ;Trp53 F/F mice because of increased macrophage-derived IL-1β stimulation of the IL-17-G-CSF axis 26 . Ectopic overexpression of IL-1β in tumors derived from cancer cell lines or a genetically engineered gastric cancer model also increases the number of circulating neutrophils [60][61][62][63] . As such, aberrant production of cytokines by tumors or stromal cells can offset the balance of neutrophil retention and release from the bone marrow.…”
Section: Neutrophil Retention and Release From Bone Marrowmentioning
confidence: 99%
“…Previous studies have demonstrated that various proinflammatory mediators, such as IL-1b (22,40), IL-6 (23), the bioactive lipid PGE 2 (24), S100A8/A9 (25,41), and complement component C5a (42), are involved in the accumulation and activation of MDSCs in tumor-bearing mice and cancer patients. However, whether TNFa, as a prototype and key proinflammatory cytokine, is also in- volved in this pathological process is still obscure.…”
Section: Discussionmentioning
confidence: 99%